Review paper on ‘Garden Kits’ in Africa: lessons learned and the potential of improved water management - Merrey, Douglas J.; Langan, Simon J. (International Water Management Institute, 2014)
The purpose of this paper is to synthesize the available knowledge and lessons learned from past experiences in promoting kitchen or home gardens for food production, with a special emphasis on water management. The benefits of home gardens for better family nutrition, health status of children and mothers, and as an entry point for empowering women have been documented in some studies. However, there is very little specific evidence to confirm these benefits. The paper also reviews some of the water management practices and garden technologies used in home and market gardens. It recommends building on current home gardening practices, starting with diagnostic appraisals of actual gardening practices, and moving on to participatory action research focused on evaluating promising water management technologies and testing implementation of strategies that empower women.